Improved understanding of particle transport in karst groundwater using natural sediments as tracers. (1st December 2019) - Goeppert, Nadine; Goldscheider, Nico
Abstract: Colloids and particles act as vectors for contaminant transport. In karst aquifers, particle transport is particularly efficient and plays critical roles in soil erosion and in the process of karstification. However, available techniques for particle tracing are either expensive or not representative for the transport of natural colloids and particles. We developed a new method for particle tracing, using natural sediments as artificial tracers, and first applied this method at a karst experimental site in the Alps. Suspended particles were injected into a swallow hole together with a conservative solute tracer for comparison. Breakthrough curves for 32 different particle size classes between 0.8 and 450 μm were recorded at a karst spring 230 m away using a mobile particle counter that allows quantitative detection at high temporal resolution. Results show that (i) sediments can be used as efficient particle tracers in karst groundwater; (ii) recoveries are similar for particles and solutes; (iii) mean velocity increases with increasing particle size; (iv) dispersion decreases with increasing particle size; (v) these observations point to exclusion processes. As a conclusion, this new experimental technique allows new insights into the transport and fate of colloids and particles in groundwater at affordable costs. Graphical abstract: Image 1 Highlights: Natural sediment particles were used as artificial tracers. Particle breakthrough curves for 32 different size classes were recorded. Mean velocities of particles increase systematically with increasing particle size. Longitudinal dispersion decreases with particles size, due to exclusion processes. The new method allows to study colloidal transport at field scale efficiently.